2011
DOI: 10.1007/s10545-011-9298-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations in patients with Gaucher disease and their relatives, it is just a coincidence?

Abstract: Gaucher disease (GD) is an autosomal recessive disorder characterized by defective function of glucocerebrosidase. GD presents a wide spectrum of manifestations, and patients and their relatives may develop neurological abnormalities more frequently than the general population. This study aims to determine the presence of neurological symptoms (NS) and Parkinson's disease (PD) in Spanish GD patients and their relatives. We surveyed 87 GD Spanish families and validated the information obtained on the neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…As we mentioned before the N370S mutation has been traditionally associated with the absence of neurological disease; however, several studies reported a high proportion of patients with the N370S mutation were diagnosed with GD 1 and showed mild neurological symptoms such tremor, peripheral neuropathy, uncoordinated movements, and hearing loss (as well as Parkinson disease. (Capablo et al, 2008;Giraldo et al, 2011;Pastores et al, 2003). These findings are consistent with the recently established contention that the mutation could not fully protect the patient from the appearance of neurological symptoms (Halperin et al, 2007).…”
Section: Mutations In Gba and Neuronopatic Forms Of Gaucher Diseasesupporting
confidence: 89%
See 3 more Smart Citations
“…As we mentioned before the N370S mutation has been traditionally associated with the absence of neurological disease; however, several studies reported a high proportion of patients with the N370S mutation were diagnosed with GD 1 and showed mild neurological symptoms such tremor, peripheral neuropathy, uncoordinated movements, and hearing loss (as well as Parkinson disease. (Capablo et al, 2008;Giraldo et al, 2011;Pastores et al, 2003). These findings are consistent with the recently established contention that the mutation could not fully protect the patient from the appearance of neurological symptoms (Halperin et al, 2007).…”
Section: Mutations In Gba and Neuronopatic Forms Of Gaucher Diseasesupporting
confidence: 89%
“…This survey revealed that a significant proportion of patients with GD I experience neurological symptoms. In addition, we found that GD1 patients have a greater risk of suffering other common unrelated diseases than carriers or their healthy relatives (Giraldo et al, 2011). The wide spectrum phenotypic variation and neurological involvement within all types, and the recognition of an increasing number of subgroups of patients, support the view that GD is a disorder with a phenotypic continuum ranging from prenatal lethality to asymptomatic adults (Sidransky, 2004).…”
Section: Other Neurological Manifestations In Type 1 Gaucher Diseasesupporting
confidence: 54%
See 2 more Smart Citations
“…БП выявляется у 1-2% населения старше 65 лет, поэтому ее относят к наиболее распространенным заболеваниям среди лиц пожилого возраста [2]. В последние годы отмечено частое сочетание БП с мутацией в гене лизосомального фермента β-глюко-цереброзидазы А (GBA) [4].…”
unclassified